REAKSI PEMERINTAHAN JOKO WIDODO-JUSUF KALLA ATAS REGULASI PASAR TUNGGAL BASIS PRODUKSI ASEAN (STUDI KASUS SEKTOR PASAR BERAS DI INDONESIA) - Ali Martin; Niki Febriyani (Universitas Wahid Hasyim Semarang, 2021)
This research is motivated by the existence of economic integration that has been agreed by ASEAN member countries to establish the ASEAN Economic Community, one of which aims to form an ASEAN Production Base Single Market in order to increase competitiveness and equalize the economy of the ASEAN community. The purpose of this study is to determine the reaction of the Joko Widodo-Jusuf Kalla government to ASEAN Single Market Production Base regulations in a case study of the rice market sector in Indonesia. The author uses descriptive qualitative research methods. The data collection technique used is literature review which comes from literature suchas books, documents, journals, articles, and the internet. Research written using qualitative analysis techniques. By giving an explanation regarding the reaction of the Joko Widodo-Jusuf Kalla government to accept the ASEAN Production Base Single Market regulation in the Indonesian ricemarket sector, with several policies summarized by the author, covering the development ofconnectivity infrastructure, increasing rice production, periodic market operations, limiting thevolume of rice imports, and determination of rice import tariffs. Keywords: Joko Widodo-Jusuf Kalla's government, ASEAN Single Market Production Base, Indonesian Rice Market